Sintering densification, grain growth, and microstructure - Kang, S.-J. L. (Suk-Joong L.) (Amsterdam ; Boston ; London : Elsevier Butterworth-Heinemann, 2005)
Sintering is the process of forming materials and components from a powder under the action of thermal energy. It is a key materials science subject: most ceramic materials and many specialist metal powder products for use in key industries such as electronics, automotive and aerospace are formed this way. Written by one of the leading experts in the field, this book offers an unrivalled introduction to sintering and sintering processes for students of materials science and engineering, and practicing engineers in industry. The book is unique in providing a complete grounding in the principles of sintering and equal coverage of the three key sintering processes: densification, grain growth and microstructure. Students and professional engineers alike will be attracted by the emphasis on developing a detailed understanding of the theory and practical processes of sintering, the balanced coverage of ceramic and metal sintering, and the accompanying examination questions with selected solutions. Delivering unrivalled depth of coverage on the basis of sintering, science, including thermodynamics and polycrystalline microstructure. Unique in its balanced coverage of the three key sintering elements - densification, grain growth and microstructure. A key reference for students and engineers in materials science and engineering, accompanied by examination questions and selected solutions.
Basis of Sintering Science; Solid State Sintering Models and Densification; Grain Growth; Microstructure Development; Sintering of Ionic Compounds; Liquid Phase Sintering.
Includes bibliographical references and index.
Keywords: Sintering; Sintering -- Problems, exercises, etc; Electronic books; Problems, exercises, etc